Neural Tube Defects: Non-Closure V. Early Closure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Non-closure of open neural tube defects above L2 in 105 infants born between 1978 and 1985 resulted in a significantly lower incidence (p < 0.001) of hydocephalus, shunt insertions, and ventriculitis during the first few months of life, and mortality was not increased throughout the first year, in a study reported from the Royal Belfast Hospital for Sick Children, Belfast, Northern Ireland.